The Species Mycobacterium africanum in the Light of New Molecular Markers - Niemann, S. (American Society for Microbiology, 2004)
The findings of recent studies addressing the molecular characteristics of Mycobacterium tuberculosis complex isolates have initiated a discussion on the classification of M. africanum, especially of those isolates originating from East Africa (cluster F, subtype II) and displaying phenotypic and biochemical characteristics more similar to those of M. tuberculosis. To further address this question, we analyzed a representative collection of 63 M. tuberculosis complex strains comprising 30 M. africanum subtype I strains, 20 M. africanum subtype II strains, 10 randomly chosen M. tuberculosis isolates, and type strains of M. tuberculosis, M. bovis, and M. africanum for the following biochemical and molecular characteristics: single-nucleotide polymorphisms (SNPs) in gyrB and narGHJI and the presence or absence of RD1, RD9, and RD12. For all molecular markers analyzed, subtype II strains were identical to the M. tuberculosis strains tested. In contrast, the subtype I strains as well as the M. africanum type strain showed unique combinations of SNPs in gyrB and genomic deletions (the absence of RD9 and the presence of RD12), which proves their independence from M. tuberculosis and M. bovis. Accordingly, all subtype I strains displayed main biochemical characteristics included in the original species description of M. africanum. We conclude that the isolates from West Africa were proved to be M. africanum with respect to the phenotypic and genetic markers analyzed, while the isolates from East Africa must be regarded as phenotypic variants of M. tuberculosis (genotype Uganda). We propose the addition of the molecular characteristics defined here to the species description of M. africanum, which will allow clearer species differentiation in the future.